Morphology and microstructure of Ag islands of aggregated atoms on oil surfaces - 张初航 吕能 张晓飞 Saida Ajeeb 夏阿根 叶高翔 (Chinese physics B, 2011)
The morphology evolution of silver islands on silicone oil surfaces is measured and the microstructure of the islands is studied. The deposited Ag atoms diffuse and aggregate on the oil surface and then Ag islands with the width of the order of 10^2-nm form. After the samples are removed from the vacuum chamber, the immediate measurement shows that the apparent Ag coverage of the total area decays with the magnitude up to （23.0±3.8）% in few minutes. In the following two hours, the samples are kept in the ambient atmosphere and several unexpected results are detected： 1） as the topological structure of the islands evolves, the total area of each island decreases gradually and the maximum decrement measured is around 20%; 2） if an island breaks and becomes two small pieces, the total area decreases obviously; 3） however, if two small islands meet and stick together, a sudden increment of the total area is observed. These phenomena, mirroring the evolution process of the island microstructure, are resulted from both the diffusion of the atoms and the combination of the defects inside the islands.